The reliability and validity of the standardized Mensendieck test in relation to disability in patients with chronic pain. (3rd August 2018) - Keessen, Paul; Maaskant, Jolanda; Visser, Bart
ABSTRACT: The standardized Mensendieck test (SMT) was developed to quantify posture, movement, gait, and respiration. In the hands of an experienced therapist, the SMT is proven to be a reliable tool. It is unclear whether posture, movement, gait, and respiration are related to the degree of functional disability in patients with chronic pain. The objective of this study was to assess the reliability and convergent validity of the SMT in a heterogeneous sample of 50 patients with chronic pain.Methods : Internal consistency was determined by Cronbach's α and interrater reliability by the intraclass correlation coefficient (ICC). Convergent validity was assessed by determining the Spearman rank correlation coefficient between the movement quality measured in the SMT and functional limitation measured on the disability rating index (DRI).Results : The internal consistency was Cronbach's α 0.91. Substantial reliability was found for the items: movement (ICC = 0.68), gait (ICC = 0.69), sitting posture (ICC = 0.63), and respiration (ICC = 0.64). Insufficient reliability was found for standing posture (ICC = 0.23). A moderate correlation was found between average test score SMT and the DRI ( r  = −0.37) and respiration and DRI ( r  = −0.45).Discussion : The SMT is a reasonably reliable tool to assess movement, gait, sitting posture, and respiration. None of the items in the domain standing posture has sufficient reliability. A thorough study of this domain should be considered. The results show little evidence for convergent validity. Several items of the SMT correlated moderately with functional limitation with the DRI. These items were global movement, hip flexion, pelvis rotation, and all respiration items.